Understanding Robert Lucas (1967-1981): his influence and influences - Alexandre F.S. Andrada (EconomiA, 2017)
This paper analyzes Robert Lucas's contribution to economic theory between 1967 (year of his first solo publication) and 1981 (the year before the emergence of Real Business Cycle approach), and it has two parts. The first one, using citation data from three different sources, we try to answer two questions: (i) What are Lucas's most influential papers currently? (ii) How has this influence changed through time? We show, for instance, that according to two of those three sources, Lucas's most influential paper today is not from his business cycle research agenda, which gave him his Nobel Prize in 1995. Moreover, it is clear the loss of influence of Lucas's macroeconomic theory since the early 1980s. In the second part, by cataloging all the works that Lucas had used as bibliographical references in his papers and separating them in two categories (positive and negative), we try to understand who exerted influence on him. We show that the author that Lucas most cited in a positive context were John Muth, Milton Friedman and Edmund Phelps. The authors more often cited in a negative context were John M. Keynes and A. W. Phillips. We discuss the reasons behind this data. – – O texto analisa as contribuiç\~oes à teoria econômica desenvolvidas por Robert entre os anos de 1967 (quando de sua primeira publicaç\~ao solo) e 1981 (ano imediatamente anterior à emergência da abordagem de ciclos reais). O artigo tem duas partes. Na primeira, fazendo-se uso de dados de citaç\~ao de três fontes distintas, tenta-se responder as seguintes quest\~oes: (i) qual artigo de Lucas – do período analisado – é hoje o mais influente? (ii) como se comportou essa influência ao longo do tempo? Mostra-se, por exemplo, que segundo duas das três fontes utilizadas, o artigo de Lucas atualmente mais influente n\~ao pertence à sua agenda de pesquisa sobre ciclos econômicos, a qual lhe garantiu o prêmio Nobel em 1995. Além disso, é clara a perda de influência da teoria de ciclos de Lucas, notadamente a partir do início dos anos 1980. Na segunda parte, após a catalogaç\~ao de todos os textos usados por Lucas como referência bibliográfica nos artigos de nossa amostra, os separamos em duas grandes categorias: citaç\~oes positivas e negativas. Os autores que Lucas mais comumente cita de maneira positiva s\~ao John Muth, Milton Friedman e Edmund Phelps. Já os autores mais comumente citados em um contexto negativo s\~ao John M. Keynes e A. W. Phillips. Analisam-se as quest\~oes pode detrás dessa observaç\~ao."
Keywords: 330; Robert Lucas; New classical macroeconomics; Citation analysis; Bibliometrics; Robert Lucas; Macroeconomia Novo Clássica; Análise de citaç\~oes; Bibliometria